Stereological and Morphometric Study of Type 3 Collagen Formation in the Cutaneous Wounds of Diabetic Mice Treated with Mesenchymal Stem Cells - Rodrigues, Huanna Waleska Soares; Neto, Napoleão Martins Argôlo; Silva, Lucilene dos Santos; Carvalho, Maria Acelina Martins de; Monteiro, Betânia Souza (Acta Scientiae Veterinariae, 2018)
Introduction: Wound healing is a progressive, essential and complex physiological process that occurs as a restorative response after a tissue injury. It involves three phases: inflammation, proliferation and maturation. Exogenous, endogenous and pathological factors may interfere in the cicatricial process in humans and animals by altering the balance between the synthesis, degradation and remodelling of collagen and elastic fibres. Diabetes mellitus is a progressive metabolic disease that alters elastogenesis and collagenesis and induces delays in the healing process. Scientific evidence suggests that mesenchymal stem cells modulate the cicatricial response. Thus the objective of this work was to perform stereological and morphometric analysis to determine the formation of dermal fibres in cutaneous fragments of a murine model of diabetes mellitus. Materials, Methods & Results: Histological sections were obtained from the cutaneous wounds of diabetic mice. The cutaneous wounds were previously treated with autogenous mesenchymal stem cells, physiological solution or polyurethane membrane. The histological sections were subsequently processed and stained for type 1 and 3 collagen fibres and elastic fibres using Picrosirius Red and Weigert staining, respectively. Histological sections stained with Picrosirius Red presented three types of birefringence under polarised light microscopy that corresponded to red colours for type 1 collagen and green and yellow colours for type 3 collagen. Weigert staining presented three colours for histological structures under white light microscopy that corresponded to black colours for elastic fibres, variations in colour from pink to purple for other structures and dermal attachments. The elastic fibres, represented by a black colour, presented in a heterogeneous form and were either identified as thin, punctiform or rectangular fibres or as elastic agglomerates. A greater volume of elastic fibres was observed in the superficial dermis than in the deep dermis, arranged irregularly. These fibres were organised longitudinally to the dermo-epidermal junction and surrounding the blood vessels and hair follicles. The images obtained were evaluated using the Cavalieri principle of stereology to obtain quantitative data in three-dimensions (3D), represented by the volume of the dermal fibres, and by the colour segmentation method. The K-means clustering plug-in in Image J® was used to quantify the area of the dermal fibres in the cutaneous wounds after the proposed dermatological treatments. A total of 90 images were obtained and analysed. No statistically significant differences (P > 0.01) were observed in the volume or area of type 1 collagen fibres between the treatment groups. Significant differences (P < 0.01) were only identified for the volumes and areas of type 3 collagen, with treated animals also presenting lower mean values for the volume and area of elastic fibres compared to the control group. Discussion: The preponderance of type 3 immature collagen in the cutaneous wounds of animals treated with stem cells indicates active collagenase and greater fibroblastic activity, which is probably induced by stem cells. Diametrically, the identification of lower levels of elastic fibres in the cutaneous fragments treated with stem cells suggests that cell therapy does not contribute satisfactorily to elastogenesis. Previous reports suggested that mesenchymal stem cells may decrease elastin synthesis, and such a situation may have occurred in this study. The autologous mesenchymal stem cells increased the formation of collagen fibres in diabetic mice at the detriment of the formation of elastic fibres, thus suggesting active early collagen in the first 2 weeks of the cicatricial process.